Origanum vulgare ethanolic extracts as a promising source of compounds with antimicrobial, anti-biofilm, and anti-virulence activity against dental plaque bacteria - Idir, Fouzia; Van Ginneken, Sybren; Coppola, Guglielmo A.; Grenier, Daniel; Steenackers, Hans P.; Bendali, Farida (Frontiers in Microbiology, 2022)
Dental caries and periodontal diseases remain a challenge for oral health, especially given the lack of effective and safe treatment options that are currently available. Against the backdrop of an ongoing antimicrobial resistance crisis, a renewed interest in traditional medicinal plants as a potential source of new bioactive compounds has surfaced. In this context, we systematically screened the antimicrobial and anti-biofilm activities of both ethanolic and aqueous extracts of nine Algerian medicinal plants (Artemisia herba alba, Centaurium erythraea, Juglans regia, Laurus nobilis, Matricaria recutita, Mentha pulegium, Mentha piperita, Origanum vulgare and Taraxacum officinale). To evaluate the activity spectrum of the extracts, the screening was carried out against an extensive collection of Streptococcus, Enterococcus and Lacticaseibacillus isolates recovered from dental plaques of Algerian patients. Broad-spectrum antimicrobial and anti-biofilm properties were observed, especially among ethanolic extracts, which marks them as a promising source for bioactive compounds to control oral biofilms. The ethanolic extract of O. vulgare, which showed the most promising effects in the initial screening, was further characterized. We first verified the biocompatibility of this extract using human oral keratinocytes and selected a range of non-cytotoxic concentrations (0.195-0.781 mg/mL) to further validate its anti-biofilm and anti-virulence potential. At these concentrations, the extract not only prevented biofilm formation (10.04±0.75-87.91±9.08% of reduction) of most dental plaque isolates on a polystyrene surface, but also significantly reduced their adherence to hydroxyapatite (34.58±9.09-62.77±0.95%). Moreover, the extract showed curative potential against mature biofilms grown under conditions mimicking the oral niche. In addition to its anti-biofilm properties, we observed an inhibition of glucosyltransferase activity, a reduction in acidogenesis and a downregulation in the expression of multiple virulence-associated genes for extract-treated samples. Since anti-virulence properties are more robust to the development of resistance, they provide an attractive complementation to the antimicrobial activities of the extract. Thymol was identified as an important active compound of the extract using GC-MS analysis, but synergy with other compounds was also detected, suggesting a potential advantage of using the whole extract over purified thymol. Further research into the bioactive compounds of the O. vulgare ethanolic extract could yield novel products to fight dental caries.